Stropharia rugosoannulata and Gymnopilus luteofolius: Promising fungal species for pharmaceutical biodegradation in contaminated water. (1st February 2018) - Castellet-Rovira, Francesc; Lucas, Daniel; Villagrasa, Marta; Rodríguez-Mozaz, Sara; Barceló, Damià; Sarrà, Montserrat
Abstract: Pharmaceuticals are environmental micropollutants that pose an emerging challenge because they are poorly eliminated in conventional wastewater treatment plants. Over the last decade, many attempts have been made to solve this problem, and wastewater fungal treatment is a promising alternative. In this study, six different ligninolytic fungi ( Trametes versicolor, Ganoderma lucidum, Irpex lacteus, Stropharia rugosoannulata, Gymnopilus luteofolius and Agrocybe erebia ) were studied as bioremediation candidates for the removal and degradation of six recalcitrant pharmaceutical micropollutants: Carbamazepine (CBZ), Venlafaxine (VFX), Iopromide (IPD), Diclofenac (DCF), Cyclophosphamide (CFD) and Ifosfamide (IFD). Self-immobilization in a pellet shape was achieved for all fungal mycelia (which was the first time that this was reported for S. rugosoannulata, G. luteofolius, and A. erebia ). Biodegradation achievement was greater than 90% for IPD with G. luteofolius and greater than 70% for CBZ with S. rugosoannulata, which suggests a great potential for this alternative biological treatment. Besides, this was the first report where fungal treatment achieved CFD and IFD removals greater than 20% for the treatment with T. versicolor, G. lucidum and S. rugosoannulata . Graphical abstract: Highlights: Three novel biodegradation candidates grown in pellet form. Biodegradation achievement greater than 90% for iopromide with G. luteofolius . More than 70% of carbamazepine degraded with S. rugosoannulata . Total removals greater than 25% for two recalcitrant cytostatics. S. rugosoannulata proved to degrade a wide range of PhACs.